Tax progression in OECD countries : an integrative analysis of tax schedules and income distributions - Seidl, Christian (Springer Berlin Heidelberg, 2013)
This is the first book that performs international and intertemporal comparisons of uniform tax progression with empirical data. While conventional measures of tax progression suffer from serious disadvantages for empirical analyses, this book extends uniform measures to progression comparisons of countries with different income distributions. Tax progression is analyzed in terms of Lorenz curve and Suits curve equivalents of net incomes and taxes. The authors derive six distinct definitions of the relation "is more progressive than", which are then utilized for an empirical analysis of 13 countries included in the Luxembourg Income Study (LIS). In two thirds of all international comparisons of tax progression, the authors report a clear ranking of the respective countries in terms of progression dominance. Tax based definitions of greater progressivity perform best. These observations are yet reinforced by statistical tests. The book also provides an account of the institutional background of the involved countries in order to facilitate the interpretation of the data. Moreover, the authors conduct intertemporal comparisons of tax progression for selected countries and perform a sensitivity analysis with respect to the parameterization of the equivalence scale.